2013
DOI: 10.1007/s00423-013-1130-1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoduodenectomy—current status of surgical and perioperative techniques in Germany

Abstract: This study revealed a distinct variety of management strategies for pancreatic surgery and available evidence-based data was not necessarily translated into clinical practice. The limited certification rate represented a shortcoming of quality assurance. The data emphasize the need for further trials to answer the questions whether hospital certifications and omission of drains improve outcome after pancreatoduodenectomy and for the establishment of guidelines for pancreatoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Pancreatic fistula (PF) after pancreaticoduodenectomy (PD) is an unsolved problem [1][2][3][4][5], associating with high mortalities as nationwide survey from United State (including 68,643 cases) and Japan (17,634 cases), report 7.6 and 2.9 %, respectively [4,6]. Recent trend in technical discussion among worldwide pancreatic surgeons seems to focus in two issues, that is the site of anastomosis (i.e., pancreaticojejunostomy vs. pancreaticogastrostomy [7][8][9]) and the way of anastomosis (i.e., two layer anastomosis with duct-to-mucosa anastomosis vs. Invagination method [10][11][12]). In addition to those methods, Japanese pancreatic First report was presented at the 66th General Meeting of the Japanese Society of Gastroenterological Surgery, Nagoya Congress Center, Nagoya, Japan, July 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic fistula (PF) after pancreaticoduodenectomy (PD) is an unsolved problem [1][2][3][4][5], associating with high mortalities as nationwide survey from United State (including 68,643 cases) and Japan (17,634 cases), report 7.6 and 2.9 %, respectively [4,6]. Recent trend in technical discussion among worldwide pancreatic surgeons seems to focus in two issues, that is the site of anastomosis (i.e., pancreaticojejunostomy vs. pancreaticogastrostomy [7][8][9]) and the way of anastomosis (i.e., two layer anastomosis with duct-to-mucosa anastomosis vs. Invagination method [10][11][12]). In addition to those methods, Japanese pancreatic First report was presented at the 66th General Meeting of the Japanese Society of Gastroenterological Surgery, Nagoya Congress Center, Nagoya, Japan, July 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical reduction with closed manipulation is achieved, but there is no agreement on the most appropriate method to ensure the continuity of reduction in unstable fractures. A meta-analysis reports that conservative treatment with cast-immobilization is adequate in elderly patients (29), but another study concluded that anatomical reduction and fixation with a volar plate is the best option (30). On the other hand, crossfire study found no difference between conservative treatment and cast immobilization in the elderly (31).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to a widely held belief that placement of intra‐abdominal drains after pancreatic surgery is beneficial, the present study shows that pancreatic resection with a pancreaticojejunostomy can be performed safely without placement of drains. However, recent surveys have demonstrated that most pancreatic surgeons around the world still use drains on a routine basis. Furthermore, there was no difference between the use of closed‐suction drains (preferred amongst surgeons in the USA) and no‐suction (passive) drains (more popular in Europe and Asia).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, intra‐abdominal drains have been used after pancreatic resection to prevent fluid accumulation and infection of fluid collections, to treat POPF, and to facilitate the detection of other intra‐abdominal complications including haemorrhage. Whereas prophylactic drainage has been abandoned for several indications in visceral surgery, most surgeons still consider it mandatory after pancreatic resection. However, abdominal drains may serve as the portal for entry of bacteria, potentially leading to infection of intra‐abdominal fluid collections.…”
Section: Introductionmentioning
confidence: 99%